Pengaruh Pemahaman Teknologi Informasi, Pendidikan, Umur Usaha Dan Motivasi Terhadap Implementasi SAK EMKM Pada UMKM Di Kabupaten Tabanan - Kadek Dela Kusumasari; I Putu Gede Diatmika (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of understanding information technology, education, business age and UMKM motivation on the implementation of SAK EMKM. This study is a quantitative study, using primary data obtained from the results of questionnaire answers with the help of google form and measured using a Likert scale. The sample of this study was selected using random sampling technique and obtained a sample of 100 respondents calculated by the Slovin formula. Primary data in the form of respondents' answers were processed using SPSS version 20. The results of this study indicate that partially understanding of information technology, education, business age, and motivation have a positive and significant effect on the implementation of SAK EMKM. The conclusion of this study, the variables of understanding of information technology, education, age of business and motivation affect the implementation of SAK EMKM on UMKM in Tabanan Regency. Keywords: Implementation of SAK EMKM, Understanding of Information Technology, Education, Age of Business, and Motivation.